Malaysian perception and attitude towards green concept and going green. - Phuah, Kit Teng; Rezai, Golnaz; Mohamed, Zainalabidin; Shamsudin, Mad Nasir (2012)
Food is the basic need for all human being and consumers have the right to choose the good quality and safe foods. The series of food safety scandal, health consciousness, environmental and animal welfare issues have caused the consumers to increasingly aware about the food they consume. Consumers begin to search for green products in the market that supposedly produced under the friendly environment and green in nature. However, it is only the beginning of the development of the green concept in Malaysia. Thus the objective of this study is to determine the relationship between the socio demographic variables towards the consumers’ attitude with regards to environmental protection, food safety concern, health consciousness and animal welfare concern. Descriptive analysis, Chi-square and binary logistic model were used to accomplish the objectives of this study. The result shows that selected socio-demographic variables such as education level, income, age and gender are significantly influence the consumers’ attitude towards health, environmental protection, food safety and animal welfare concern. The results also indicate that subjective norm, education level, income, attitude towards health, food safety and environmental concern are the factors that influence consumers’ attitude towards green concept.